Practical neurology - Biller, J. Jose (Wolters Kluwer, 2017)
Put key neurology information at your fingertips and successfully apply it in practice with Practical Neurology, Fifth Edition . This popular reference is a concise complement to core neurology texts, providing easy access to the clinically relevant information you need to know. Organized in a reader-friendly outline format with straightforward, templated chapters, this edition contains new chapters that highlight recent advances in neurotherapeutics and clinical neurosciences, 82 new clinical videos, and fully updated content throughout.